APPROXIMATION TO THE SYNTAXONOMICAL SCHEME OF THE VEGETATION FROM CARIBBEAN REGION AND SOUTH AMERICA - Galán de Mera, Antonio; Vicente Orellana, José A. (Anales de Biología, 2006)
In this work, we present a preliminary phytosociological synthesis of the vegetation of the Caribbean region and South America to the alliance level. As result, we can recognize 95 phytosociological classes. For the moment, as novelties, 6 new classes (Alnetea acuminatae Calamagrostio effusae-Espeletietea grandifl orae, Chiliotrichetea diffusi, Gaultherio-Aristotelietea, Palauo dissecti-Nolanetea gayanae and Pruno rigidae-Oreopanecetea fl oribundae), 2 orders Andropogono multinervosi- Eragrostietalia cubensis and Cortaderietalia jubatae) and 3 alliances (Najo guadalupensis-Ruppion maritimae, Polylepidion incano-pautae and Pruno tucumanensis-Alnion acuminatae) are described.